Putusan Hakim dalam Memutus Perkara di Luar Dakwaan Jaksa Penuntut Umum - Juniansyah, Edo; Zahri, Saipuddin (Universitas Batanghari Jambi, 2024)
Judges in deciding cases outside the indictment of the public prosecutor must be based on justice. The formulation of the problems in this study are 1) How is the judge's decision in deciding cases outside the indictment of the public prosecutor? 2) What is the philosophical, sociological and juridical basis for categorizing criminal verdicts outside the indictment of the public prosecutor as a legal formation? The research method used is normative juridical research. The data sources used in this research consist of secondary data. Based on the research results, it shows that 1) The judge's decision in deciding cases outside the indictment of the public prosecutor in the practice of its application, the judge has a basic reason for legal considerations that lead to a sense of legal justice for the community. Criminal decisions outside the indictment of the public prosecutor according to applicable progressive law have a strong legal position based on the principle or principle of freedom of judges to examine and decide cases. and 2) The philosophical, sociological and juridical foundations categorize criminal decisions outside the indictment of the public prosecutor as a legal formation, namely the judge in examining and deciding cases is obliged to apply legal provisions, so that they have a basis for deciding criminal cases outside the indictment of the Public Prosecutor as a legal formation.